Nonlinear heart rate variability measures under electromagnetic fields produced by GSM cellular phones. (June 2013) - Parazzini, Marta; Ravazzani, Paolo; Thuroczy, György; Molnar, Ferenc B.; Ardesi, Gianluca; Sacchettini, Alessio; Mainardi, Luca Tommaso
<x xml:space="preserve">Abstract</x> This study was designed to assess the nonlinear dynamics of heart rate variability (HRV) during exposure to low-intensity EMFs. Twenty-six healthy young volunteers were subjected to a rest-to-stand protocol to evaluate autonomic nervous system in quiet condition (rest, vagal prevalence) and after a sympathetic activation (stand). The procedure was conducted twice in a double-blind design: once with a genuine EMFs exposure (GSM cellular phone at 900 MHz, 2 W) and once with a sham exposure (at least 24 h apart). During each session, three-lead electrocardiograms were recorded and RR series extracted off-line. The RR series were analyzed by nonlinear deterministic techniques in every phase of the protocol and during the different exposures. The analysis of the data shows there was no statistically significant effect due to GSM exposure on the nonlinear dynamics of HRV.